B7H6-specific bispecific T cell engagers (BiTEs) lead to tumor elimination and host anti-tumor immunity(),2 - Wu, Ming-Ru (2015)

(untitled) (J Immunol)
Substantial evidence showed that T cells are the key effectors in immune-mediated tumor eradication. However, most T cells do not exhibit anti-tumor specificity. In this study, a bispecific T cell engager (BiTE) approach was utilized to direct T cells to recognize B7H6+ tumor cells. B7H6 is a specific ligand for the NK cell activating receptor, NKp30. B7H6 is expressed on various types of primary human tumors, including leukemia, lymphoma, and gastrointestinal stromal tumors (GISTs), but it is not constitutively expressed on normal tissues. In this study, data show that B7H6-specific BiTEs direct T cells to mediate cellular cytotoxicity and IFN-γ secretion upon co-culturing with B7H6+ tumors. Furthermore, B7H6-specific BiTE exhibited no self-reactivity to pro-inflammatory monocytes. In vivo, B7H6-specific BiTE greatly enhanced the survival benefit of RMA/B7H6 lymphoma bearing mice through perforin and IFN-γ effector mechanisms. In addition, long term survivor mice were protected against a RMA lymphoma tumor re-challenge. The B7H6-specific BiTE therapy also decreased tumor burden in murine melanoma and ovarian cancer models. In conclusion, B7H6-specific BiTE activates host T cells and has the potential to treat various B7H6+ hematological and solid tumors.